ctg(x/2)-tg(x/2)-2tg(x)=4 с объяснением

ctg(x/2)-tg(x/2)-2tg(x)=4 с объяснением

  • ctg(x/2) — tg(x/2) — 2*tg(x) = 4

    (1+cosx)/(sinx) — (1-cosx)/(sinx) — 2 * sinx/cosx = 4

    (1+cosx-1+cosx)/(sinx) — 2*sinx/cosx =4

    2*(cosx — sinx)/(sinx*cosx)=4

    2*cos(2x)/(2sinx*cosx)=2

    ctg(2x)=1

    2x =/4 + n, n Z

    x =/8 +*n/2,n Z

    Ответ:/8 +*n/2, n Z

    Формулы:

    ctg(x/2) = (1+cosx)/sinx

    tg(x/2) = (1-cosx)/sinx

    sin 2x = 2sinx*cosx

    cos 2x = cosx — sinx

    ctg(x) = a

    x = arcctg(a) +n, n Z

Share

About admin

Добавить комментарий

Ваш e-mail не будет опубликован. Обязательные поля помечены *